PENGEMBANGAN MEDIA KOMIK BERGAMBAR MATERI SISTEM SARAF UNTUK PEMBELAJARAN YANG MENGGUNAKAN STRATEGI PQ4R - Wahyuningsih, Ary Nur (JPP, 2011)
The problem of this experiment is Ã¢â‚¬Å“How to develop teaching learning media with pictorialcomic on human nerve system to be applied in teaching learning process using PQ4Rstrategy to increase studentsÃ¢â‚¬â„¢ learning result, activity and interest?Ã¢â‚¬Â one of the purposethis experiment is to develop teaching learning media pictorial comic on human nervesystem material to be applied using valid, effective and practical PQ4R strategy. Thisdeveloping experiment was R&D. The source of the data involved three biology teachers,six students of small class and forty students of big class. The validity involved twoexperts; material experts and media experts. The result of the experiment showed thatteaching learning media with pictorial comic on human nerve system material could increaselearning result mastering of students. It could be seen from gaining medium score,increasing of studentsÃ¢â‚¬â„¢ activity, increasing of studentsÃ¢â‚¬â„¢ interest and achieving positive responsefrom students and teacher.Keywords :teaching learning comics, human nerve system, PQ4R strategy, learning result,teaching learning media